Growing Up Under Parental Care: Understanding Parenting Dynamics in the Lives of LGBTQ + Individuals - Rahma, Shafa Aulia; Purwandari, Eny (Universitas Islam Negeri Raden Intan Lampung, 2023)
LGBT is an acronym for Lesbian, Gay, Bisexual, and Transgender which is obtained from the Ministry of Health of Indonesia data in the past period, the number of LGBT in the last few decades has increased and has begun to express themselves with their existence in public. Many parents have not been able to accept their children's different sexual orientation, but in fact many people have a non-heterosexual sexual orientation and are not in general. The purpose of this study is to analyze how parenting affects LGBT sexual orientation. The subjects in this study amounted to 7 people, namely 4 parents and 3 children who have gay, lesbian, and transgender sexual orientation aged ±18-25 years. This research uses a qualitative approach with a phenomenological approach with interpretative phenomenological analysis (IPA) data analysis techniques and extracting data with in depth interviews. The results showed that parental care that affects a person's sexual orientation is the absence of a father figure in the child's life and an irresponsible father who cannot be used as a role model by the child so that the child thinks that the father is an irresponsible figure. However, this is not the only factor in changing a person's sexual orientation because hormonal factors which are internal factors from a person can also be one of the factors that make a person have a lesbian, gay, bisexual, or transgender sexual orientation. From the results of the study, it can be concluded that parental care is one of the contributing factors for someone to have a non-heterosexual sexual orientation, but it is not the only factor because there are internal factors that are also one of the contributing factors for someone to have a non-heterosexual sexual orientation. Keywords: parenting, sexual orientation, LGBT